Analysis of restriction profiles of DNA of local isolates of Sporothrix schenkii - Sit, M. L.; Mutalib, Abdul Rahim; Omar, Abdul Rahman; Bahaman, Abdul Rani (Universiti Putra Malaysia Press, 2004)
Restriction fragment length polymorphism (RFLP) patterns of the fungus, Sporothrix schenkii were investigated by digestion with restriction enzyme, HaeIII. Based on the RFLP patterns, twelve isolates, collected from sporotrichotic cats in Klang Valley, were found to be of the same type with similar patterns.